2019
DOI: 10.3390/su11051248
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Supply Chain Integration and Internal Control on Financial Performance in the Jordanian Banking Sector

Abstract: The aim of this paper is to use a recently developed framework of supply chain integration (SCI) to examine the influence of a set of relationships between SCI and internal control on financial performance in the Jordanian banking sector. SCI consists of external integration and internal integration. External integration includes customer integration and supplier integration. This study utilizes survey data from 249 employees in the Jordanian banking sector and tests the research framework and hypotheses using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 47 publications
5
32
0
1
Order By: Relevance
“…Moreover, Franek & Kashi (2018) conclude that even new hybrid methods may be used to evaluate corporate performance. The study of Bae et al (2019) showed that high leverage is associated with substantial losses in market share due to unfavourable actions by customers and competitors; financial performance is investigated in the study of Pakurar et al (2019) CENTRAL EUROPEAN BUSINESS REVIEW and Sadaf et al (2018). Moreover, they revealed the effect of corporate social responsibility on the leverage level, which verifies the results of Xu et al (2015).…”
Section: Literature Reviewsupporting
confidence: 53%
“…Moreover, Franek & Kashi (2018) conclude that even new hybrid methods may be used to evaluate corporate performance. The study of Bae et al (2019) showed that high leverage is associated with substantial losses in market share due to unfavourable actions by customers and competitors; financial performance is investigated in the study of Pakurar et al (2019) CENTRAL EUROPEAN BUSINESS REVIEW and Sadaf et al (2018). Moreover, they revealed the effect of corporate social responsibility on the leverage level, which verifies the results of Xu et al (2015).…”
Section: Literature Reviewsupporting
confidence: 53%
“…Many studies have indicated that, internal integration facilitates superior intra-firm coordination and collaboration between dissimilar functions, which improves performance in the firm (Huo et al , 2015; Pakurár et al , 2019; Song and Song, 2020). This could be attained through sharing of integrational data and cross-departmental collaboration (Schoenherr and Swink, 2012; Ebrahimi, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the past, CSR research has mainly been conducted at the macro-institutional level [8] and has mostly focused on the link between CSR and corporate financial [9,10] and competitive performance [11]. Researchers have mainly concentrated on the external component of CSR and the interests of external stakeholders by addressing issues such as environmental sustainability [12], corporate philanthropy [13] and community development [14].…”
Section: Introductionmentioning
confidence: 99%